Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Kartu Seluler Simpati (Studi Kasus Mahasiswa Prodi Manajemen Fakultas Ekonomi Universitas Batanghari Jambi) - Donny Novits Aswad; Osrita Hapsara; M Alhudhori (Science of Management and Students Research Journal (SMS), 2019)
This research was conducted to find out the quality of the product and the price on the cellular card sympathy for your purchasing decision in the student environment. due to the large number of cellular cards circulating in the student environment.The method used in this research is the study of literature’s, a study conducted by using literature and writer’s that is closely related to the object of study, which is intended to obtain studid. Besides theory and information sourced from the internet.Batanghari university since its inception 1985 to date, is fostered by and shelter under jambi education foundation. This foundation is a development of jambi education foundation which was foemerly built STKIP Jambi 1970-1977. Based on the results of multiple linear regression analysis states that y = 1,112 + 0,199 x1 + -0,087 x2 + e, with R square 74,9%, product quality and price influence the purchase decision on sympathetic cellular cards simultaneously, with a value of 9,360 and a significant level 0,001 . whereas partially only product quality has an influence on purchasing decisions with a value of 2.922 and a significant level of 0.010. The influence of product quality and price simultaneously affect purchasing decisions because the value of the calculation of 9,134> ftabel 3,10. Independent factors can explain the dependent factor by 78.7% while the remaining 21.3% is caused by other factors while partially the quality of the product has a positive and significant effect on the purchase decision of the sympathetic cellular card, this is evidenced by the value of t count 3.730> t table 1.66159 and states that h1 is accepted and h0 is rejected.